Resonant Scattering in Proximity‐Coupled Graphene/Superconducting Mo2C Heterostructures - Meng Hao; Chuan Xu; Cheng Wang; Zhen Liu; Su Sun; Zhibo Liu; Hui‐Ming Cheng; Wencai Ren; Ning Kang (Advanced Science, 2022)
Abstract The realization of high‐quality heterostructures or hybrids of graphene and superconductor is crucial for exploring various novel quantum phenomena and devices engineering. Here, the electronic transport on directly grown high‐quality graphene/Mo2C vertical heterostructures with clean and sharp interface is comprehensively investigated. Owing to the strong interface coupling, the graphene layer feels an effective confinement potential well imposed by two‐dimensional (2D) Mo2C crystal. Employing cross junction device geometry, a series of resonance‐like magnetoresistance peaks are observed at low temperatures. The temperature and gate voltage dependences of the observed resonance peaks give evidence for geometric resonance of electron cyclotron orbits with the formed potential well. Moreover, it is found that both the amplitude of resonance peaks and conductance fluctuation exhibit different temperature‐dependent behaviors below the superconducting transition temperature of 2D Mo2C, indicating the correlation of quantum fluctuations and superconductivity. This study offers a promising route toward integrating graphene with 2D superconducting materials, and establishes a new way to investigate the interplay of massless Dirac fermion and superconductivity based on graphene/2D superconductor vertical heterostructures.